Sulphur Assisted Nitrogen-Rich CNF for Improving Electronic Interactions in Co-NiO Heterostructures Toward Accelerated Overall Water Splitting - Surendran, Subramani; Jesudass, Sebastian Cyril; Janani, Gnanaprakasam; Kim, Joon Young; Lim, Yoongu; Park, Jihyun; Han, Mi Kyung; Cho, In Sun; Sim, Uk (Advanced Materials Technologies, 2023)
Electrochemical water splitting is the eco-friendly route to generate green hydrogen, which is recognized as sustainable energy for the future. However, the cost, operational efficiency, and long-term durability of the electrochemical water splitting rely on the choice of the electrocatalysts. Hence, developing a superior design strategy is an important criterion to establish an efficient and sustainable water splitting system. Herein, a sulphur-rich Co NiO heterostructure encapsulated on N-rich carbon nanofibers (SCNO@N-CNF) synthesized via a simple and efficient electrospinning technique is reported. The three-way redox active centers, viz., the electron redistributed active Coδ- NiOδ+ interfaces, S-dopant sites with modified electronic density, and the porous N-CNF matrix, makes the prepared electrocatalyst more efficient toward oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). The SCNO@N-CNF electrocatalyst exhibits a low OER and HER overpotentials (ηOER = 247 mV; ηHER = 169 mV) at a current density of 10 mA cm−2. Moreover, SCNO@N-CNF was analyzed as the bifunctional electrocatalyst in overall electrochemical water splitting, and it is found to deliver 10 mA cm−2 at only 1.58 V. Thus, the design and engineering of multiple active elements in a single electrocatalyst is anticipated as an effective approach to establish an efficient and sustainable water splitting system.
Keywords: Bifunctional electrocatalysts; Carbon nanofibres; Co-NiO heterostructure; Eco-friendly; Electrochemicals; Electronic interactions; Hydrogen evolution reactions; Sustainable water; Water splitting; Water splitting system; bifunctional electrocatalyst; carbon nanofiber; Co-NiO heterostructure; electrospinning; water splitting